SYSTEMATIC LITERATURE REVIEW OPTIMALIMASI LITERASI DIGITAL UNTUK EFISIENSI PENANGGULANGAN CYBERBULLYING - lim, sheren; Pernando, Yongky (J-Com (Journal of Computer), 2025)
Abstract: This study aims to review digital literacy as a strategy to prevent cyberbullying in adolescents using the Systematic Literature Review (SLR) approach to research from 2020 to 2024. Cyberbullying, which often occurs verbally, is influenced by the anonymity of the perpetrator and low digital literacy. The results of the study show that digital literacy can increase students' awareness, self-control, understanding of privacy, and empathy in interacting in the digital world. Psychosocial support from family, school, and community is also key in preventing cyberbullying. This study emphasizes the importance of digital literacy as an effective strategy to build responsible attitudes and positive interactions in the digital world. Keywords: systematic literature review; digital literacy; cyberbullyingAbstrak: Penelitian ini bertujuan untuk meninjau literasi digital sebagai strategi pencegahan cyberbullying pada remaja dengan pendekatan Systematic Literature Review (SLR) terhadap penelitian tahun 2020 hingga 2024. Cyberbullying, yang kerap terjadi secara verbal, dipengaruhi anonimitas pelaku dan rendahnya literasi digital. Hasil penelitian menunjukkan bahwa literasi digital dapat meningkatkan kesadaran, pengendalian diri, pemahaman privasi, serta empati siswa dalam berinteraksi di dunia digital. Dukungan psikososial dari keluarga, sekolah, dan masyarakat juga menjadi kunci dalam mencegah cyberbullying. Penelitian ini menegaskan pentingnya literasi digital sebagai strategi efektif untuk membangun sikap bertanggung jawab dan interaksi positif di dunia digital.  Kata kunci: systematic literature review; literasi digital; cyberbullying